2020
DOI: 10.1177/0306624x20964143
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Drug Use among Offenders in Some Prisons in Ghana

Abstract: Among others, the study sought to find out whether being convicted of the possession of marijuana for personal use for the first time or multiple times, would predict marijuana, and other drug use within the past 30 days. Using a cross-sectional survey, two hundred and fifty three (253) male offenders were conveniently sampled from three prisons in Ghana. The average age of participants was 31.26 (SD = 10.19). It was established that those who had been convicted of the possession of marijuana for personal use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Similar reasons, such as boredom, coping mechanisms, depression, harsh prison conditions and lack of meaningful activities, addiction, peer pressure and overcrowding have been found in other studies (Boakye et al, 2022;Rowell-Cunsolo et al, 2016;Skowroński & Talik, 2018). Parimah et al (2020) found that prisoners convicted of possessing cannabis for personal use for the first time were likely to have used substances within the past 30 days; about a third had used cannabis and nearly one fifth had used other drugs. The authors further reported an association between recidivism and other substance use.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar reasons, such as boredom, coping mechanisms, depression, harsh prison conditions and lack of meaningful activities, addiction, peer pressure and overcrowding have been found in other studies (Boakye et al, 2022;Rowell-Cunsolo et al, 2016;Skowroński & Talik, 2018). Parimah et al (2020) found that prisoners convicted of possessing cannabis for personal use for the first time were likely to have used substances within the past 30 days; about a third had used cannabis and nearly one fifth had used other drugs. The authors further reported an association between recidivism and other substance use.…”
Section: Introductionsupporting
confidence: 74%
“…Parimah et al. (2020) found that prisoners convicted of possessing cannabis for personal use for the first time were likely to have used substances within the past 30 days; about a third had used cannabis and nearly one fifth had used other drugs. The authors further reported an association between recidivism and other substance use.…”
Section: Introductionmentioning
confidence: 99%